Epitaxial magnetic oxide nanocrystals via phase decomposition of bismuth perovskite precursors - Bogle, Kashinath A.; Cheung, Jeffrey; Chen, Yong-Lun; Liao, Sheng-Chieh; Lai, Chih-Hung; Chu, Ying-Hao; Gregg, John M.; Ogale, Satishchandra B.; Valanoor, Nagarajan (Advanced Functional Materials, 2012)
The phase instability of bismuth perovskite (BiMO3), where M is a ferromagnetic cation, is exploited to create self-assembled magnetic oxide nanocrystal arrays on oxide supports. Conditions during pulsed laser deposition are tuned so as to induce complete breakdown of the perovskite precursor into bismuth oxide (Bi2O3) and metal oxide (M-Ox) pockets. Subsequent cooling in vacuum volatizes the Bi2O3 leaving behind an array of monodisperse nanocrystals. In situ reflective high energy electron diffraction beam is exploited to monitor the synthesis in real-time. Analysis of the patterns confirms the phase separation and volatization process. Successful synthesis of M-Ox, where M = Mn, Fe, Co, and Cr, is shown using this template-free facile approach. Detailed magnetic characterization of nanocrystals is carried out to reveal the functionalities such as magnetic anisotropy as well as larger than bulk moments, as expected in these oxide nanostructures.
Keywords: Bi2O3 evaporation; bismuth perovskites; epitaxial nanostructures; magnetic oxides; phase separation